2016
DOI: 10.3390/f7030049
|View full text |Cite
|
Sign up to set email alerts
|

White Spruce Growth and Wood Properties over Multiple Time Periods in Relation to Current Tree and Stand Attributes

Abstract: Abstract:The relationships between white spruce radial increment and wood properties were investigated in relation to tree and stand attributes using data from mature white spruce stands in the boreal forest of western Canada that experienced a range of shelterwood treatments. The model with the highest predictive ability was radial increment (adj-R 2 = 67%) and included crown attributes, diameter at breast height (DBH), average height of competitors, and a climate index. Radial growth was positively related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…(Tanabe et al, 2017). Stiffness has also been associated with cambial age, ring density, ring width, proportion of corewood and stem slenderness in white spruce (Zhou and Smith, 1991, Sattler et al, 2014b, Cortini et al, 2016. In Norway spruce (Picea abies (L.) Karst.…”
Section: Bending Strength and Stiffnessmentioning
confidence: 99%
“…(Tanabe et al, 2017). Stiffness has also been associated with cambial age, ring density, ring width, proportion of corewood and stem slenderness in white spruce (Zhou and Smith, 1991, Sattler et al, 2014b, Cortini et al, 2016. In Norway spruce (Picea abies (L.) Karst.…”
Section: Bending Strength and Stiffnessmentioning
confidence: 99%
“…4). It must also be mentioned that according to the methodology of estimating density separately for earlywood and latewood it did not reflect the typical negative correlation to increased secondary growth induced by higher temperatures as found in other studies ( Cortini et al, 2016 ; Hassegawa et al, 2019 ). DEN showed similar but overall relatively weaker reactions to climate conditions than CWT.…”
Section: Discussionmentioning
confidence: 59%
“…Intracoenotic factors connected with intra-and interspecific competition between trees are also important resulting in the differentiation of individuals in terms of growth rate and vitality status (Demidko et al 2010;Das 2012;Hereş et al 2018). Several authors found a significant correlation between stem radial growth and main indicators of vitality status of conifer trees such as crown density (Demidko 2011;Cortini et al 2016;Donnelly et al 2017) and needle mass (Vanninen 2004). Using Pinus sibirica Du Tour as an example, Demidko et al (2010) showed that the radial increment in strongly weakened individuals at the age of 60 and 140 years is 35% and 65% lower than in healthy ones.…”
Section: Introductionmentioning
confidence: 99%